2018
DOI: 10.1016/j.vaccine.2018.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a plant-produced Pfs25 virus-like particle as a transmission blocking vaccine against malaria: A Phase 1 dose-escalation study in healthy adults

Abstract: HighlightsReport of a Phase I clinical trial to assess a malaria transmission blocking vaccine.P. falciparum Pfs25 virus-like particle produced under cGMP in a plant-based system.The vaccine candidate displays an acceptable safety and tolerability profile.The vaccine candidate induced Pfs25-specific IgG in a dose dependent manner.However, low transmission reducing activity implies need for an improved formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 32 publications
1
68
0
Order By: Relevance
“…The existing vaccine, RTS,S, has demonstrated only limited efficacy in clinical trials [17]. A recent publication [53] summarizes the results of a Phase I study assessing a malaria transmission-blocking vaccine based on a recombinant fusion of the P. falciparum antigen Pfs25 with the plant virus AlMV. Vaccine candidates produced in whole plants under cGMP conditions demonstrate acceptable safety and tolerability and induce antibodies against Pfs25, depending on the injected vaccine dose.…”
Section: Plant Vlp-derived Vaccines Against Infectious Diseasesmentioning
confidence: 99%
“…The existing vaccine, RTS,S, has demonstrated only limited efficacy in clinical trials [17]. A recent publication [53] summarizes the results of a Phase I study assessing a malaria transmission-blocking vaccine based on a recombinant fusion of the P. falciparum antigen Pfs25 with the plant virus AlMV. Vaccine candidates produced in whole plants under cGMP conditions demonstrate acceptable safety and tolerability and induce antibodies against Pfs25, depending on the injected vaccine dose.…”
Section: Plant Vlp-derived Vaccines Against Infectious Diseasesmentioning
confidence: 99%
“…In contrast to the PEV and BSV vaccines, which have already been assayed in completed Phase III trials, the assays of the Pfs25 antigen are in early development and so far, have only completed Phase I trial assays, though with success. In one of them, the Pfs25 protein was engineered as a VLP, manufactured in Nicotiana benthamiana plants, and was formulated with Alhydrogel (63). In a second Phase I trial, Pfs25 was conjugated to the recombinant, detoxified ExoProtein A from Pseudomonas aeruginosa (64).…”
Section: Tbv Vaccinesmentioning
confidence: 99%
“…NCT02013687). The initial trials using Alhydrogel formulations of Pfs-EPA or Pfs25-VLP showed that they were safe but did not stimulate robust TBA titers, and these results have led to the testing of alternative adjuvants, including AS01 (113)(114)(115).…”
Section: Gametocyte/gamete Antigens Pfs230 Pfs48/45 Pfs47 and Hap2mentioning
confidence: 99%